Modular and regioselective synthesis of all-carbon tetrasubstituted olefins enabled by an alkenyl Catellani reaction - Wang, Jianchun; Dong, Zhe; Yang, Cheng; Dong, Guangbin (Nature chemistry, 2019)
All-carbon tetrasubstituted olefins have been found in numerous biologically important compounds and organic materials. However, regio- and stereocontrolled construction of this structural motif still constitutes a significant synthetic challenge. Here, we show that a modular and regioselective synthesis of all-carbon tetrasubstituted olefins can be realized via alkenyl halide- or triflate-mediated palladium/norbornene catalysis, which is enabled by a modified norbornene containing a C2 amide moiety. This new norbornene co-catalyst effectively suppressed undesired cyclopropanation pathways, which have previously been a main obstacle for developing such reactions. Diverse cyclic and acyclic alkenyl bromides or triflates with a wide range of functional groups can be employed as substrates. Various substituents can be introduced at the alkene C1 and C2 positions regioselectively simply by changing the coupling partners. Initial mechanistic studies provide insights on the rate-limiting step as well as the structure of the actual active ligand in this system. All-carbon tetrasubstituted olefins are challenging to prepare in a regio- and stereocontrolled fashion. Now, using an amide-substituted norbornene as a co-catalyst, alkenyl halide- or triflate-mediated palladium/norbornene (Pd/NBE) catalysis has been demonstrated, providing an efficient strategy for modular and regioselective construction of all-carbon tetrasubstituted olefins.